The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1038/ki.2010.525
|View full text |Cite
|
Sign up to set email alerts
|

Persistent proteinuria and dyslipidemia increase the risk of progressive chronic kidney disease in lupus erythematosus

Abstract: Advances in immunotherapy have improved survival of patients with systemic lupus erythematosus who now face an increasing burden of chronic diseases including that of the kidney. As systemic inflammation is also thought to contribute directly to the progression of chronic kidney disease (CKD), we assessed this risk in patients with lupus, with and without a diagnosis of nephritis, and also identified modifiable risk factors. Accordingly, we enrolled 631 patients (predominantly Caucasian), of whom 504 were diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 44 publications
(79 reference statements)
5
47
1
Order By: Relevance
“…The role of sustained proteinuria as a prognostic marker in SLE nephritis has been recently proposed [57,58]: our results suggest that this parameter independently predicts the risk of late or non-remission in populations of patients receiving heterogeneous treatments.…”
Section: Discussionsupporting
confidence: 53%
“…The role of sustained proteinuria as a prognostic marker in SLE nephritis has been recently proposed [57,58]: our results suggest that this parameter independently predicts the risk of late or non-remission in populations of patients receiving heterogeneous treatments.…”
Section: Discussionsupporting
confidence: 53%
“…Partial renal response, defined as ≥50% reduction in proteinuria to subnephrotic levels and normal or near-normal GFR, should be achieved preferably by 6 months and no later than 12 months following treatment initiation 9 33–35. Improvement includes any reduction in proteinuria and normalisation or stabilisation of GFR.…”
Section: Resultsmentioning
confidence: 99%
“…Such outcomes, however, are not frequent and may occur late in the course of LN. Intermediate outcome measures, such as renal response and flares, occurring in the majority of patients within the first 2 years after treatment initiation, correlate with hard outcomes in studies with long-term follow-up and are commonly used as endpoints in trials 9 33–35 37–39 44. Correlation does not guarantee surrogacy of these outcomes for all patients, some of whom may still have hard outcomes diverging from their intermediate outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of as Cr ≤ 1.0 mg/dl to the 24H-P<0.8 g/day target increased the specificity (87%) but lowered the sensitivity (78%) for the prediction of good renal prognosis at 12 months, suggesting that the degree of proteinuria is of utmost importance for the development of CKD. Reich et al, showed that the time-averaged proteinuria was the predictor of the rate of progression of renal function decline [59], with higher decline for higher proteinuria: subjects with 24H-P 0-1 g/day losing 1.15 ± 5.37 ml/min per 1.73 mt 2 per year of GFR vs subjects with 24H-P > 2.0 g/day losing 6.68 ± 14.6ml/min per 1. highlighted the importance of persistent proteinuria and indicated that in the short term, proteinuria is a predictor of doubling creatinine and developing CKD. Recently, Touma et al, showed that the development of long-term renal outcomes (e.g.…”
Section: Proteinuria In Lupus As a Prognostic Factor For Renal Outcomesmentioning
confidence: 99%